Complementary networks for person re-identification - Zhang, Guoqing (2023)
Recently, person re-identification (re-ID) has gained much attention for its extensive applications in public security. In order to mine more detailed information, some researches have attempted to extract local representations from important regions through human semantic parsing. However, some valuable visual cues beyond human body, such as backpacks and handbags, which can provide complementary information for recognition, may be misclassified as background noise. In addition, when meeting low-quality captured images or severe occlusions, the semantic regions generated by parsing model are not accurate enough, even resulting in disturbance. In this paper, we present complementary networks for person re-ID, which aims to extract more discriminative and robust local representations with complementary clues. Our model contains two branches and one of which aims to mine potential discriminative information in the background that is useful for identifying a person, as a complement for foreground semantics of human body parts. Another branch is designed to capture the salient regions in global scope so as to make up for the problem of poor discrimination of representations caused by the inaccurate semantic confidence maps of former branch. Experiments show that our model achieves competitive performance in many cases.